Derivation of parameters used in Spectrum for eligibility for antiretroviral therapy and survival on antiretroviral therapy. (23rd November 2010) - Mahy, Mary; Lewden, Charlotte; Brinkhof, Martin W G; Dabis, Francois; Tassie, Jean-Michel; Souteyrand, Yves; Stover, John
Abstract : Background: The Spectrum projection package uses estimates of national HIV incidence, demographic data and other assumptions to describe the consequences of the HIV epidemic in low and middle-income countries. The default parameters used in Spectrum are updated every 2 years as new evidence becomes available to inform the model. This paper reviews the default parameters that define the course of HIV progression among adults and children in Spectrum. Methods: For adults, data available from published and grey literature and data from the ART-LINC International epidemiologic Database to Evaluate AIDS (IeDEA) collaboration were combined to estimate survival among those who started antiretroviral therapy (ART). For children, a review of published material on survival on ART and survival on ART and cotrimoxazole was used to derive survival probabilities. Historical data on the distribution of CD4 cell counts and CD4 cell percentages by age among children who were not treated (before treatment was available) were used to progress children from seroconversion to different CD4 cell levels. Results: Based on the updated evidence estimated survival among adults aged over 15 years in the first year on ART was 86%, while in subsequent years survival was estimated at 90%. Survival among children during the first year on ART was estimated to be 85% and for subsequent years 93%. Discussion: The revised default parameters based on additional data will make Spectrum estimates more accurate than previous rounds of estimates.